The genesis and the development of a rugby rivalry between New Zealand and South Africa before the apartheid era (1899-1948) : construction of identities, imperial power games and racial discrimination - (:unkn) unknown (My University, 2022)
Since its inception, the rugby rivalry between South Africa and New Zealand has been much written about because of its complex and peculiar nature. Over the years, a number of historians (Nauright, 1993; Buckley, 1996; Dobson, 1996), sports journalists (Labuschagne, 1974; Harding & Williams, 2000), activists (Thompson, 1975; Richards, 1999) and even politicians (Templeton, 1998) have examined its history. Most of them usually situate the starting point of this unique duel in 1921, when the first New Zealand tour by the South African national rugby team took place. In this thesis, I wish to show that competitions between these two former British colonies began much earlier, as soon as the first rugby matches were played between New Zealanders and South Africans during the Second Boer War (1899-1902). These tournaments raise at least three socio-political questions through which I analyze, in a chronological order, the history of rugby exchanges between two nations under, construction (Renan, 1882; Hobsbawm, 1990). The aim is, on the one hand, to highlight the process that led to the representation of the South African and New Zealand rugby unions within the international rugby body (International RugbyFootball Board). On the other hand, I examine the evolution of racial relations between players of European origin and indigenous players. Finally, I focus on the creation of national identities in two former territories of the British Empire, which emancipated themselves from the central London-based power at different rates. Using digitized archives, I thus attempt to trace the origins of this rugby rivalry and the racism that characterizes it while shedding light on the logic of imperial domination that were exercised on both the colonist and the colonized (Gleyse, 2004).
Keywords: African Research